Validação do instrumento SQAS (Service Quality Assessment Scale) para o cenário brasileiro - Fett, Marcelo André (2014)
The increase in the number of gyms is a worldwide and Brazilian phenomenon. Knowing the quality of the service of this segment is important both economically and for the health area. The objective of the present study was to analyze the applicability of the Service Quality Assessment Scale (SQAS): An Instrument for Evaluating Service Quality of Health-Fitness Clubs of the services offered by gyms and Health Clubs from Brazil. Methods: A questionnaire containing 40 SQAS questions based on 6 dimensions was applied. The sample comprised participants (n = 417) from six gyms in the state of Mato Grosso, Brazil. Results: Through an exploratory factor analysis (AFE) of the data collected, six factors emerged after the removal of some items, with 35 items with a coefficient of 0.40 or higher, without double loading: Personal (8 items, = 0.873), Program (5 items, = 0.929), Locker room (5 items, = 0.829), Physical Installation/Building (6 items, = .877), Training Area (5 items, = 0.981), Children's Space (6 items, α = 0.981). Conclusion: The revised Brazilian version of the SQAS includes 35 items and presented consistent psychometric properties. All these items are important for the entrepreneur to develop their business, with emphasis on children's space items and program, which have obtained the highest psychometric indexes. The SQAS has the ability to point out the items that weigh the most for the evaluation of the customers for the service received.